2017
DOI: 10.1037/pag0000161
|View full text |Cite
|
Sign up to set email alerts
|

Animalistic dehumanization of older people by younger ones: Variations of humanness perceptions as a function of a target’s age.

Abstract: The present work investigated associations of older people with humanness. Focusing on complementary approaches (attribute-based, metaphor-based, and target-based), 4 studies tested the hypothesis that older people are the targets of animalistic dehumanization. Using an emotional attribution task, Study 1 (N = 112) explored infrahumanization and shows that young participants attributed more uniquely human emotions to young people than to older ones. No such effect occurred with regards to nonuniquely human emo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
2
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(24 citation statements)
references
References 61 publications
0
19
2
2
Order By: Relevance
“…This trend is most likely a consequence of the high percentage of self-objectification studies, mainly derived from a feminist approach with a stronger focus on women. Indeed, very few studies have looked at men or older adults as victims of dehumanization, even though older people are more often dehumanized than young people (Boudjemadi, Demoulin, & Bastart, 2017) and men may also be denied humanness (Capozza, Falvo, Trifiletti, & Pagani, 2014; Fasoli et al, 2016). This trend is at odds with most social psychology studies that typically focus on social minority groups, who are at an increased risk of dehumanization (Diniz, Castro, Bousfield, & Bernardes, under review; Haslam, 2006; Haslam & Loughnan, 2014; Haslam & Stratemeyer, 2016; Volpato, Andrighetto, & Baldissarri, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…This trend is most likely a consequence of the high percentage of self-objectification studies, mainly derived from a feminist approach with a stronger focus on women. Indeed, very few studies have looked at men or older adults as victims of dehumanization, even though older people are more often dehumanized than young people (Boudjemadi, Demoulin, & Bastart, 2017) and men may also be denied humanness (Capozza, Falvo, Trifiletti, & Pagani, 2014; Fasoli et al, 2016). This trend is at odds with most social psychology studies that typically focus on social minority groups, who are at an increased risk of dehumanization (Diniz, Castro, Bousfield, & Bernardes, under review; Haslam, 2006; Haslam & Loughnan, 2014; Haslam & Stratemeyer, 2016; Volpato, Andrighetto, & Baldissarri, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…The experiment is a 2 (priming type: Congruent vs. incongruent) x 2 (target type: Death-related words vs. negative words) within subject design. We estimated the sample size on the basis of previous work using a similar design (112 participants in Boudjemadi et al, 2017). Power analysis indicated that this sample size is sufficient to detect a small to medium effect size with 95% power.…”
Section: Methods Participantsmentioning
confidence: 99%
“…Attributing another person less mental capacity or less moral status often parallels comparisons of that person with nonhuman entities such as animals, robots or objects (Boudjemadi et al, 2017;Loughnan et al, 2014;Morris et al, 2018;Heflick & Goldenberg, 2009;. For some people, these dehumanizing perceptions can justify that a person or group is treated inhumanely.…”
Section: Prejudice Against Sex Work and The Dehumanization Of Womenmentioning
confidence: 99%